2016
DOI: 10.1111/eff.12320
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐induced seasonal changes in smallmouth bass growth rate potential at the southern range extent

Abstract: Temperature increases due to climate change over the coming century will likely affect smallmouth bass (Micropterus dolomieu) growth in lotic systems at the southern extent of their native range. However, the thermal response of a stream to warming climate conditions could be affected by the flow regime of each stream, mitigating the effects on smallmouth bass populations. We developed bioenergetics models to compare change in smallmouth bass growth rate potential (GRP) from present to future projected monthly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Although we found that the selection of warmer waters during autumn is important to Smallmouth Bass, we acknowledge that cooler water facilitated by groundwater features is important during the warmer seasons (Brewer 2013b; Middaugh et al. ) and may also be important at other latitudes during winter or in especially cold years at this latitude (e.g., Westhoff et al. ).…”
Section: Discussionmentioning
confidence: 72%
“…Although we found that the selection of warmer waters during autumn is important to Smallmouth Bass, we acknowledge that cooler water facilitated by groundwater features is important during the warmer seasons (Brewer 2013b; Middaugh et al. ) and may also be important at other latitudes during winter or in especially cold years at this latitude (e.g., Westhoff et al. ).…”
Section: Discussionmentioning
confidence: 72%
“…Our simulations indicate that increases in drought frequency could strongly affect abundance of smallmouth bass in the Buffalo River. Previous work has documented a decline in body condition of smallmouth bass during summer months in some streams in the Ozark region, including the upper Buffalo River [ 50 ], and it is likely that increasing stream temperature due to climate change will decrease growth potential of smallmouth bass during summer months [ 28 ]. Drought conditions can stress fish and result in population declines [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also assume that relationships between May temperature and June discharge and smallmouth bass recruitment will be the same in the future as during the period that data was collected. The Buffalo River is a runoff stream and other stream types, such as intermittent or groundwater dominated, could have different responses to climate change than runoff streams (e.g., temperature, [ 28 ]). Another simplifying assumption occurs in the way we model harvest mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change models for the southeastern United States predict an increase in the number and duration of droughts, greater mean annual air temperature, as well as an increased frequency of heavy rain events with shorter durations in the future [9]. The impacts of a potentially changing climate on Ozark bass populations are unknown at this time, but studies have suggested other sport fish may expand their habitat range and exhibit changes in growth rate potential [10].…”
Section: Introductionmentioning
confidence: 99%